2021
DOI: 10.2147/oaem.s315228
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and Outcome of Acute Appendicitis: Observational Prospective Study from a Teaching Hospital, Addis Ababa, Ethiopia

Abstract: Background Acute appendicitis is the most common cause of acute abdomen surgery. Despite its commonness and the abundance of literature on the subject, its diagnosis remains challenging. Delay in intervention results in complications of the process leading to increased morbidity and mortality. Methodology An observational prospective cohort study was conducted, and all patients who had undergone appendectomy for a clinical diagnosis of appendicitis were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
2
1
1
Order By: Relevance
“…Dagebo et al at St. Luke Catholic Hospital in Woliso, Ethiopia, reported a 10.4-day duration for complications compared to a 6.6-day duration for simple cases (35). The study found that complicated cases (27.6%) typically present after 48 hours (p > 0.00), with illness duration significantly influencing intraoperative findings, similar to the study done in our hospital (50), in Woliso, Oromia, Ethipoia (35).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Dagebo et al at St. Luke Catholic Hospital in Woliso, Ethiopia, reported a 10.4-day duration for complications compared to a 6.6-day duration for simple cases (35). The study found that complicated cases (27.6%) typically present after 48 hours (p > 0.00), with illness duration significantly influencing intraoperative findings, similar to the study done in our hospital (50), in Woliso, Oromia, Ethipoia (35).…”
Section: Discussionsupporting
confidence: 86%
“…The study found that the role of temperature and relative humidity in seasonal variation was weaker, similar to the research conducted in Bahrain (10). typically present after 48 hours (p > 0.00), with illness duration significantly influencing intraoperative findings, similar to the study done in our hospital (50), in Woliso, Oromia, Ethipoia (35).…”
Section: Table 12: Displays Frequency Of Post-operative Complications...supporting
confidence: 85%
See 1 more Smart Citation
“…At the beginning of the 21st century, the incidence of appendicitis was seen to grow in newly industrialized countries. Moreover, mortality, morbidities, and the imposed economic impact associated with appendicitis have been reported in western countries [ 8 ]. Fits described appendicitis first-time more than 100 years ago, and 561,000 appendectomies per year were conducted between 1979–1984 in the United States, representing that different etiological agents might have had hands in this regard [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute appendicitis is among the most common causes of emergency abdominal surgery. 1 Worldwide, the total pooled incidence of appendicitis or appendectomy is around 100–150 per 100,000 person-years. 2 Recent studies suggest a rise in the prevalence of appendicitis in developing countries between the early teenage years and the late 40s.…”
Section: Introductionmentioning
confidence: 99%